أساس وجوهر مبدأ مسؤوليّة الحماية - خازم, نور الدين; ستيتي, نغم (Latakia University Journal - Economic and Legal Sciences Series, 2019)
فشِل المجتمعُ الدُّولي في تحقيق الحماية اللّازمة لحقوق الإنسان لاسيما أثناء النِّزاعات المُسلَّحة غير الدُّولية, ما دفعه إلى تكريس الجهود للبحث عن آليّة جديدة أكثر قبولاً و فاعليّة لحماية حقوق الإنسان, وقد تُوّجت بالتّوصل إلى مبدأ جديد في التّصدِّي للانتهاكات الخطيرة والمُمنهجة لحقوق الإنسان والقانون الدُّولي الإنساني, عُرف هذا المبدأ الجديد باسم مسؤوليّة الحماية . ويعدُّ مبدأ مسؤوليّة الحماية أسلوباً حديثاً منبثقاً عن تطوّر مفاهيم التّدخُّل الدُّولي الإنساني, وهو يهدف إلى حماية الأفراد من أكثر الجرائم الدُّولية انتهاكاً لحقوقهم والمتمثّلة بجرائم الإبادة الجماعيّة, والتّطهير العرقي, وجرائم الحرب, والجرائم ضدَّ الإنسانيّة, ويرتكز المبدأ في جوهره على مسؤوليّة الدُّولة أوّلاً في حماية مواطنيها بصفتها صاحبة السّيادة, و تنتقل المسؤوليّة إلى واجب المجتمع الدُّولي بالرّد والاستجابة في حال عدم قدرة الدّولة أو رغبتها في تحقيق تلك الحماية, حيث يبدأ الرّدُ سلمياً لكنّه قد ينتهي إلى التّدخل العسكريِّ وفق معايير وضوابط محدّدة . The failure of the international community to achieve the necessary protection of human rights, especially during non-international armed conflicts, has led to the search for a new, more acceptable and effective mechanism for the protection of human rights and culminated in a new principle in addressing serious and systematic violations of human rights and international humanitarian law, This new principle has been defined as protection responsibility. The principle of responsibility for protection is a modern method stemming from the development of the concepts of international humanitarian intervention. It aims at protecting individuals from the most serious international crimes in violation of their rights of genocide, ethnic cleansing, war crimes and crimes against humanity. And responsibility is transferred to the international community's duty to respond and respond in the event of its inability or desire to achieve such protection, where the response begins peacefully but may end up in military intervention according to the criteria and they I specific.